Caracterização do padrão molecular e de virulência de isolados de Pyricularia grisea do trigo - Cruz, Maria Fernanda Antunes da (2008)
Wheat blast caused by Pyricularia grisea, was described in Brazil in the 80th, in Parana State. Since then, the wheat breeding programs have searched for sources of resistance to blast, and try to understand the pathogen variability. The gols of this work were: a) to determine virulence pattern of 18 isolates of P. grisea based on the inoculation reaction of 70 young wheat genotypes, b) to verify the resistance level to blast of synthetic and common wheat genotypes at young and adult plant stages, c) to relation the results of both stages d) to determine the molecular pattern of 31 P. grisea isolates. The molecular pattern of the 18 monosporic isolates of P. grisea based on 8 loci microsatellites presented 75% of similarity among isolates. The molecular and virulence pattern were similar based on the results of 70 wheat seedling inoculation. Exception was observed with Py 5002 isolate. This isolate molecular pattern didn t match with other isolates, presenting 32% of similarity. The genotypes BRS 229, BRS 179, CNT 8, BRS 120, BRS Buriti, presented better performance in young plant compared to the others genotypes. The synthetic wheat adult genotypes (NE 20156-B, PF 844001, PF 964009, PF 804002) and cultivar CNT 8 presented less leaf and head infected area by blast. There was 54% of correlation index between flag leaf and head was 54%. The data obtained in this research indicated the at existence different resistance genes are expressed in different physiological stages of wheat the plant